2011
DOI: 10.1038/npp.2011.188
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Aversive Effects of Cannabidiol on Innate Fear-Induced Behaviors Evoked by an Ethological Model of Panic Attacks Based on a Prey vs the Wild Snake Epicrates cenchria crassus Confrontation Paradigm

Abstract: Several pharmacological targets have been proposed as modulators of panic-like reactions. However, interest should be given to other potential therapeutic neurochemical agents. Recent attention has been given to the potential anxiolytic properties of cannabidiol, because of its complex actions on the endocannabinoid system together with its effects on other neurotransmitter systems. The aim of this study was to investigate the effects of cannabidiol on innate fear-related behaviors evoked by a prey vs predator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
68
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 53 publications
10
68
0
4
Order By: Relevance
“…The anxiety enhancing effect of CB 1 R disruption seemed to be specific to young mice in one [26] and to aversive conditions in another study [27]. Two studies did not detect anxiety-like behavior in CB 1 The down-regulation of endocannabinoid signaling by the CB 1 R antagonist rimonabant (SR141716A) results in biphasic effects. Low doses (0.3-3 mg/kg) reduced anxiety in several models, e.g.…”
Section: Decreased Endocannabinoid Activitymentioning
confidence: 96%
See 1 more Smart Citation
“…The anxiety enhancing effect of CB 1 R disruption seemed to be specific to young mice in one [26] and to aversive conditions in another study [27]. Two studies did not detect anxiety-like behavior in CB 1 The down-regulation of endocannabinoid signaling by the CB 1 R antagonist rimonabant (SR141716A) results in biphasic effects. Low doses (0.3-3 mg/kg) reduced anxiety in several models, e.g.…”
Section: Decreased Endocannabinoid Activitymentioning
confidence: 96%
“…While the overwhelming majority of studies were likely identified, the database created by this search is probably incomplete. This figure does not include studies on the phytocannabinoid cannabidiol 1 .…”
Section: Introductionmentioning
confidence: 96%
“…These effects partially depended on 5-HT 1A R activation but were not affected by CB 1 R blockade. CBD was also panicolytic in the predator-prey model, which assesses explosive escape and defensive immobility in response to a boa constrictor snake, also partially via 5-HT 1A R activation; however, more consistent with an anxiogenic effect, CBD was also noted to decrease time spent outside the burrow and increase defensive attention (not shown in Table 1) [75,86] . Finally, CBD, partially via CB 1 Rs, decreased defensive immobility and explosive escape caused by bicuculline-induced neuronal activation in the superior colliculus [89].…”
Section: Pd and Compulsive Behavior Modelsmentioning
confidence: 97%
“…Indeed, CBD's antianxiety properties have been substantiated by elevated plus-maze and rat Vogel conflict tests [41][42][43]. The reduction of fear-related behaviors evoked by the prey/ predator paradigm also suggests some panicolytic properties [45]. CBD improves performance in numerous animal models of cognitive impairments [30,[46][47][48].…”
Section: Cbd and Neurobiological Targets/effectsmentioning
confidence: 99%